Pop-up question on educational physics video: Effect on the learning performance of students - Alif Syaiful Adam (Universitas Muhammadiyah Malang, 2022)
Pop-up question video has been developed in oscillation physics concept to support the student’s learning objection in a Junior High School level. This video use as learning source to support the information gaining in particular use of learning design. This study aimed to analyzes the effect of physics pop-up question video relating to oscillation to the student’s learning performance. Furthermore, this video developed based on the recommendation of previous research to decrease the students’ cognitive load. Besides, this particular research aimed to measure the students’ learning performance on 100 students in junior high school level. Learning performance consists of the concept attainment of oscillation concept, students’ motivation and students’ cognitive load atter pass the learning process with pop-up question video. As results, the students’ concept attainment in a percentage of 74% and stated in a good category. Then, the students’ motivation has the percentage of 84% and state in a good category while the cognitive load percentage on 38% and stated in a less category. It means, the pop-up question video has good impact on students’ motivation and has a less cognitive load simultaneously. However, for gaining the better result, pop-up question video can be integrating to the innovative learning model.